Comparative Analysis of Planning as an Administrative Task Performance by Heads in Rural and Urban Second Cycle Schools in Ghana - Sey, Vera Rosemary Ankoma- (American Journal of Education and Learning, 2019)
Effective planning is essential in the smooth running of second cycle schools in Ghana. The study examined planning as an administrative task performance by heads in the rural and urban second cycle schools in Ghana. The study sought to examine whether there is a significant difference in the level of planning by heads in the rural and urban second cycle schools in Ghana. A descriptive survey was employed as the study design. The study was targeted to 519 public second cycle schools in Ghana. Using a stratified and census sampling technique, 1085 assistant heads, heads of department and teachers were selected from 155 public second cycle schools to participated in the study. A questionnaire was used as the main instrument where respondents were required to show their level of agreement to some statements. The overall opinion of respondents revealed that planning, as administrative task performance of headteachers, was to some extent is carried out well. An independent t-test analysis revealed a statistically significant difference (p<.001) in the level of planning by heads in the rural and urban second cycle schools in Ghana. Based on the findings, was recommended that second cycle schools in the rural areas in Ghana should be given equal advantages in terms of good classroom blocks, adequate learning materials, well-equipped science and language laboratories.